The Value of Mouse Models of Rare Diseases: A Spanish Experience - Murillo-Cuesta, Silvia; Artuch, Rafael; Asensio, Fernando; de la Villa, Pedro; Dierssen, Mara; Enríquez, Jose Antonio; Fillat, Cristina; Fourcade, Stéphane; Ibáñez, Borja; Montoliu, Lluis; Oliver, Eduardo; Pujol, Aurora; et al. (Frontiers in Genetics, 2020)
Animal models are invaluable for biomedical research, especially in the context of rare diseases, which have a very low prevalence and are often complex. Concretely mouse models provide key information on rare disease mechanisms and therapeutic strategies that cannot be obtained by using only alternative methods, and greatly contribute to accelerate the development of new therapeutic options for rare diseases. Despite this, the use of experimental animals remains controversial. The combination of respectful management, ethical laws and transparency regarding animal experimentation contributes to improve society’s opinion about biomedical research and positively impacts on research quality, which eventually also benefits patients. Here we present examples of current advances in preclinical research in rare diseases using mouse models, together with our perspective on future directions and challenges.